2012
DOI: 10.1007/s12639-012-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

A serological study of Leishmania infantum in dogs of Khorasan Razavi province, Iran

Abstract: Leishmania infantum is the principal agent of visceral leishmaniosis (kala-azar) in all areas of Iran. The disease is endemic in Fars, Ardabil, East Azerbaijan and Bushehr provinces while it is sporadic in other parts of the country. Dog as a member of canidae family is the main animal reservoir host of kala-azar. The present study was carried out to determine the sero-prevalence of canine leishmaniosis in Mashhad, the capital city of Khorasan Razavi Province, in the north east of Iran. Two-hundred and nine do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In addition, it may be related to higher CO2 production, attracting vector insects [76,89,217,221], which is also observed in bigger dogs as they have a larger contact area, making them more susceptible to bites [38,157,222]. In relation to sex, several authors found no difference between male and female with the risk of infection [182,183,189,210,[223][224][225].…”
Section: Figurementioning
confidence: 99%
“…In addition, it may be related to higher CO2 production, attracting vector insects [76,89,217,221], which is also observed in bigger dogs as they have a larger contact area, making them more susceptible to bites [38,157,222]. In relation to sex, several authors found no difference between male and female with the risk of infection [182,183,189,210,[223][224][225].…”
Section: Figurementioning
confidence: 99%
“…This is also observed in larger dogs, as they have a larger contact area, making them more susceptible to bites [ 38 , 130 , 195 ]. In relation to sex, several authors found no difference between males and females regarding the risk of infection [ 152 , 153 , 159 , 181 , 196 , 197 , 198 ].…”
Section: Factors Influencing the Territorial Expansion And Transmissi...mentioning
confidence: 99%
“…Approximately every year 500,000 new cases of VL occur in the world (Barati et al 2015;Ghatee et al 2013). In the zoonotic pattern, reservoirs are dogs and rodents (Postigo 2010;Reithinger et al 2007;Sabzevari et al 2013). Evidence has shown that dogs can act as a natural host for MVL, and human is its accidental host (Fig.…”
Section: Introductionmentioning
confidence: 99%